The Effect of Consumer Ethnocentrism and Materialism on Product Brand Perception and Brand Preferences in Surabaya - Erlangga, Imron Najib (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: The purpose of the research is to examine the effect of consumer ethnocentrism and materialism to product brand perception and preferences in Surabaya as the second largest city in Indonesia. This research tests the validation of the construct measures and associated hypothesis using survey data from 132 respondents and using structural equation modeling techniques. The results show that (1) there's no correlation between consumer ethnocentrism and materialism in Surabaya, (2) consumer ethnocentrism has significant effect on product brand perception, (3) consumer ethnocentrism has not affected on product brand preferences, (4) materialism has significant effect on product brand perception, and (5) materialism has significant effect on product brand preferences. Keywords: Consumer Ethnocentrism, Materialism, Product Brand Perception, Product Brand Preferences